Laparoscopic longitudinal pancreaticojejunostomy for chronic pancreatitis: Systematic review of the literature. Issue 3 (June 2020) - Ramia, Jose M.; Azagra, J.S.; De la Plaza, R.; Manuel, A.; Latorre, R.; Lopez-Marcano, A.
Abstract: Background: Longitudinal pancreaticojejunostomy, also known as modified Puestow or Partington-Rochelle procedure, is a technique for the treatment of chronic pancreatitis. It is usually performed by laparotomy, but in a very small number of cases it has been performed using a laparoscopic or robot-assisted approach. We carried out a systematic literature review to clarify the current status of laparoscopic longitudinal pancreatojejunostomy (LLPJ). Methods: Adhering to the PRISMA guidelines, a systematic search for LLPJ was performed in PubMed, Embase, and Cochrane Library, for articles published up to 31 December 2017. Results: 357 articles were evaluated for eligibility and 17 were included for critical appraisal: eight case reports, eight retrospective case series, and one series of cases and controls without randomization. All of them had a grade of recommendation C and a level of evidence 4 according to the CEBM. Patients were relatively young (mean age 37 years), with a slight preponderance of males (ratio 1.3: 1). All had long-standing disease, ERCP prior to surgery and a dilated pancreatic duct (mean 11 mm). The surgery was usually performed laparoscopically using four trocars; the conversion rate was low (5%), bleeding was minimal, the morbidity rate was 11% and no mortality was reported. Mean hospital stay was 5.6 days. The follow-up period varied but was usually short (less than two years). The results for pain control were very good since 90% of patients reported no pain, although visual analog scales were rarely used. Conclusions: In conclusion, LLPJ seems to be a safe, feasible and effective technique in patients with chronic pancreatitis. However, the number of descriptions published to date is very small, and there are no studies with high scientific evidence comparing LLPJ with open surgery or with endoscopic treatment that would allow us to draw firmer conclusions at the present time.